Developmental model of elite athletes: The integration of developmental science and practitioner experience. - Houltberg, B. J.; Scholefield, R. M. (Professional Psychology: Research and Practice, 2020)
The demands of elite athletics often overshadow the developmental stages of children, teens, and young adults. Additionally, many athletes experience an existential crisis of questioning the psychological costs of elite competition when there are significant tensions between their developmental needs and sporting demands. It can be a difficult time for the elite athlete and create disruptions in their support system. We propose this moment as an important window of opportunity for elite athletes to redefine their motivation through a greater sense of purpose. We also discuss the important developmental processes that intersect with the elite athlete`s sport-specific experience that can inform practitioners working with elite athletes. Although there are developmental models that provide broad overviews of sport participation, there is a need for integrative models that include developmental science and applied experience. The Developmental Model of Elite Athletes was initially designed to help athletes navigate their athletic careers with clarity, consciousness, and eventually purpose. It is hoped that practitioners can use this model to support their work with elite athletes, inform coaches and parents, and help avoid the tendency to pathologize what are typical developmental experiences of elite athletes. Finally, we hope practitioners will see elite athlete questioning as an opportunity to help the athlete connect to their purpose and find healthy ways to meet their needs so they can thrive in sport and life.